Relation between grades of intervertebral disc degeneration and occupational activities of patients with lumbar disc herniation - Papić, Monika; Papić, Vladimir; Kresoja, Milena; Munteanu, Valerija; Mikov, Ivan; Cigić, Tomislav (Vojnosanitetski pregled, 2018)
Background/Aim. Intervertebral disc degeneration (IDD) occurs as consequence of combined effects of genetic, age-related, environmental and occupational factors. Lumbar disc herniation (LDH) develops mostly due to IDD. The aim of this study was to investigate whether the frequency of LDH is higher at the level of the most pronounced IDD, and whether a category of physical workload influences higher IDD on level L3-L4, L4-L5 and L5-S1 separately. Methods. The research included 60 patients with permanent employment, hospitalized due to LDH. A grade of IDD was assessed by lumbosacral preoperative magnetic resonance imaging (MRI), according to Pfirmann's MRI classification system. Occupational factors were determined by a specific questionnaire. Results. Out of the 60 patients participating in the study, 33.3% had jobs with easy workload, 23% had moderate workload, while 43% had heavy workload. Herniated discs were found at level L3-L4 in 8.3%, at level L4-L5 in 46.7% and at level L5-S1 in 45% patients. The symptomatic discs at level L5-S1 showed statistically significant frequency of degenerative changes of grades IV and V. Binary logistic regression results showed that the strongest predictor of IDD grade for examined levels was physical workload. Positive association of physical workload and IDD grade was observed in all cases. Higher grades of IDD are more likely for patients with both higher TE and heavier physical workload (OR 2.011) at level L3-L4. At levels L4-L5 and L5-S1 higher degree of IDD was more likely for females with heavier physical workload (OR 1.978 and 2.433 respectively). Conclusion. Symptomatic discs show higher frequency of higher grades of IDD but herniation does not occur solely at the disc of the most prominent degenerative changes. The results suggest importance of inter-influence of physical workload and the years of employment and the inter-influence of physical workload and gender, on degeneration of lumbar discs.
Keywords: lumbosacral region; inervertebral disc degeneration; occupational exposure; intervertebral disc displacement